1977
DOI: 10.1126/science.188133
|View full text |Cite
|
Sign up to set email alerts
|

Slow Persistent Infection Caused by Visna Virus: Role of Host Restriction

Abstract: Proviral DNA has been demonstrated by in situ hybridization in foci of cells of a lamb infected with the RNA slow virus visna. A few of these cells also contain the major virion structural antigen p30. This restriction in virus gene expression in the infected animal provides a mechanism for persistence of virus in this chronic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

1978
1978
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(50 citation statements)
references
References 13 publications
2
46
0
2
Order By: Relevance
“…Virus gene expression in the brain of these sheep was detected by in situ hybridization and infectious virus was detected by coculture of brain homogenates with susceptible cells. The low level of detectable viral gene expression is consistent with the restricted viral replication that is the hallmark of lentivirus infection (Haase et al, 1976;Johnson et al, 1996). In vitro studies demonstrated that this brain-adapted virus replicated more ef®ciently in microglia and less ef®ciently in GSM than the parental virus.…”
Section: Discussionmentioning
confidence: 92%
“…Virus gene expression in the brain of these sheep was detected by in situ hybridization and infectious virus was detected by coculture of brain homogenates with susceptible cells. The low level of detectable viral gene expression is consistent with the restricted viral replication that is the hallmark of lentivirus infection (Haase et al, 1976;Johnson et al, 1996). In vitro studies demonstrated that this brain-adapted virus replicated more ef®ciently in microglia and less ef®ciently in GSM than the parental virus.…”
Section: Discussionmentioning
confidence: 92%
“…However, the biologic relevance of these findings has been questioned by other workers who have discovered spread of virus in blood and CSF unabated by neutralizing antibodies (Petursson et al, 1976), long-term persistence of parental viral strains even after the appearance of variants (Lutley et al, 1983) and lack of antigenic variants in some animals even during advanced stages of disease (Thormar et al, 1983). Given the complexities of chronic retroviral-induced disease (Haase et al, 1977;Brahic et al, 1981;Stowring et al, 1985) it is likely that intrinsic viral characteristics as well as host-viral immune interactions play important roles in clinical outcome.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of inflammation in the choroid plexus or any other part of the brain by routine histology, in conjunction with the morphological appearance of the labelled cells makes it very unlikely that these cells are other than choroid plexus epithelial cells. The presence of SRV-1 in such cells was not entirely unexpected since retroviral infection of the choroid plexus has been demonstrated in visna of sheep (Haase et al, 1977) and because it is a pathway into the brain (Levine, 1987). In addition, SRV-1 has a broad cellular tropism in vivo (Maul et al, 1988) and an affinity for secretory epithelium such as salivary gland acinar cells (Lackner et al, 1988;Lerche et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…As shown by immunohistochemistry, the apparent source of the virus is relatively rare infected choroid plexus epithelial cells. Whether or not there is restriction of viral replication in other choroid plexus cells as there is for visna virus (Haase et al, 1977) awaits future studies involving combined in situ hybridization and immunohistochemistry. The lack of inflammation in the choroid plexus or any other part of the brain by routine histology, in conjunction with the morphological appearance of the labelled cells makes it very unlikely that these cells are other than choroid plexus epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation